2023
DOI: 10.1039/d3tc02060f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement in efficiency and photostability of organic solar cells by modifying the ZnO electron-transport layer with curcumin

Yue Liu,
Hang Yang,
Yue Wu
et al.

Abstract: As a representative electron transport layer (ETL), Zinc oxide (ZnO) has been widely used in inverted organic solar cells (i-OSCs), while its surface defects and intrinsic “light-soaking” issues have yet...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The reduced emission of the SAM-treated ZnO at wavelengths between 400 and 500 nm, when compared to the pure ZnO films, suggests the formation of new intragap states, which could lead to nonradiative recombination. Previous studies, including those by Wei et al 24 and others, 29,32 have shown that SAM treatment of ZnO can introduce intragap states. Moreover, SAM modification of ZnO may affect the electrical conductivity of the ZnO surface.…”
Section: ■ Introductionmentioning
confidence: 94%
“…The reduced emission of the SAM-treated ZnO at wavelengths between 400 and 500 nm, when compared to the pure ZnO films, suggests the formation of new intragap states, which could lead to nonradiative recombination. Previous studies, including those by Wei et al 24 and others, 29,32 have shown that SAM treatment of ZnO can introduce intragap states. Moreover, SAM modification of ZnO may affect the electrical conductivity of the ZnO surface.…”
Section: ■ Introductionmentioning
confidence: 94%
“…In the modern scientific era, integrating multifunctional applications into a unified system is the key to unlocking future advancements. 1–3 Recently, the combination of photodetectors and gas sensing has been of particular interest owing to its potential to revolutionize next-generation optoelectronic gas sensors. 4 Conventional inorganic conductometric gas sensors encounter issues such as high power consumption and poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO possesses a unique combination of low cost, minimal toxicity, high transparency, appropriate work function, great conductivity, and ease of solution preparation. 2 However, the practical use of bare ZnO nanostructures in photodetector applications is hindered by its high resistivity, low charge collection probability, large band gap, and inherent structural defects, which negatively impact the photoresponse. One viable solution to circumvent these drawbacks is doping ZnO with elements such as fluorine, chlorine, nickel, aluminium, titanium, gallium, and indium to enhance carrier mobility and, consequently, improve photosensitivity.…”
Section: Introductionmentioning
confidence: 99%